What factors must be considered in 'return to school' following concussion and what strategies or accommodations should be followed? A systematic review. Issue 4 (2nd March 2018) - Purcell, Laura K; Davis, Gavin A; Gioia, Gerard A
Abstract : Objective: To evaluate the evidence regarding (1) factors affecting return to school (RTS) and (2) strategies/accommodations for RTS following a sport-related concussion (SRC) in children and adolescents. Design: A systematic review of original studies specifically addressing RTS following concussion in the paediatric and sporting context. Data sources: MEDLINE (Ovid), Embase (Ovid), PsycInfo (Ovid) electronic databases and the grey literature OpenGrey, ClinicalTrials.gov and Google Advanced. Eligibility criteria: Studies were included if they were original research on RTS following SRC in children aged 5–18 years published in English between 1985 and 2017. Results: A total of 180 articles were identified; 17 articles met inclusion criteria. Several factors should be considered for RTS after concussion, including: symptomatology; rest following injury; age/grade; and course load. On RTS after concussion, 17%–73% of students were provided academic accommodations or experienced difficulty with RTS. Students were more likely to obtain academic accommodations in schools with a concussion policy if they had a medical RTS letter and had regular medical follow-up after concussion. Conclusions: Schools should have a concussion policy and offer individualised academic accommodations to students recovering from SRC on RTS; a medical letter should be provided to facilitate provision/receipt of academic accommodations; students should have early, regular medical follow-up following SRC to help with RTS and monitor recovery; students may require temporary absence from school after SRC; clinicians should assess risk factors/modifiers that may prolong recovery and require more intensive academic accommodations. PROSPERO registration number: CRD42016039184 .